2003
DOI: 10.1007/s00520-004-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

The ten most common adverse drug reactions (ADRs) in oncology patients: do they matter to you?

Abstract: ADRs are common in hospitalised oncology patients and are predictable and at least probably preventable in many instances. Improved use of preventative measures has the potential to contribute to reducing the incidence and severity of ADRs. Recognition and understanding of the discrepancy that exists between clinical severity and patient-perceived severity of ADRs will enable specific areas to be identified and targeted for vigourous intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 14 publications
4
79
0
2
Order By: Relevance
“…Also on further individualised specification as per adverse effect the present study depicts gastrointestinal system to be affected the most which include constipation, nausea, vomiting followed by general body disorders like fatigue which is comparable to the result depicting the most prominent adverse effects were constipation, nausea, vomiting, fatigue, alopecia and drowsiness in the study carried out by Lau et al, [25].…”
Section: Discussionsupporting
confidence: 80%
“…Also on further individualised specification as per adverse effect the present study depicts gastrointestinal system to be affected the most which include constipation, nausea, vomiting followed by general body disorders like fatigue which is comparable to the result depicting the most prominent adverse effects were constipation, nausea, vomiting, fatigue, alopecia and drowsiness in the study carried out by Lau et al, [25].…”
Section: Discussionsupporting
confidence: 80%
“…Another study reports constipation as the chief ADE. 34 Since chemotherapy usually affects organ systems with rapid cell turnover like mucus membrane, bone marrow, skin and its appendages ADEs like alopecia, myelosupression and oral ulceration are anticipated. Platinum compounds caused many ADEs in this study in correlation with the South Indian and Nepalese study which reports platinum compounds and nitrogen mustard to cause most ADEs.…”
mentioning
confidence: 99%
“…Surindiran et al reported cervical cancer as the commonest cancer [16] The differences found in our study may be due to variation in geographic regions, food habits and life styles, occupational and environmental conditions Commonest ADR reported in our study were nausea & vomiting 17.11 % .followed by Headache 8.02% , Anxiety and Diziness 6.95 %. Few other studies reported nausea & vomiting as the commonest ADR [17,18] . Cancer chemotherapy causes damage to rapidly dividing cells of the bone marrow and gastrointestinal epithelium .…”
Section: Discussionmentioning
confidence: 99%